Determinants of blood telomere length in antiretroviral treatment‐naïve HIV‐positive participants enrolled in the NEAT 001/ANRS 143 clinical trial. Issue 10 (18th September 2019) - Alejos, B; Stella‐Ascariz, N; Montejano, R; Rodriguez‐Centeno, J; Schwimmer, C; Bernardino, JI; Rodes, B; Esser, S; Goujard, C; Sarmento‐Castro, R; De Miguel, R; Esteban‐Cantos, A; et al.
Abstract : Objectives: Our aim was to investigate factors associated with baseline blood telomere length in participants enrolled in NEAT 001/ANRS 143, a randomized, open‐label trial comparing ritonavir‐boosted darunavir (DRV/r) plus raltegravir (RAL) with DRV/r plus tenofovir disoproxil fumarate/emtricitabine (TDF/FTC) in antiretroviral therapy (ART)‐naïve HIV‐positive adults. Methods: A cross‐sectional study of 201 randomly selected participants who had stored samples available was carried out. We measured telomere length (i.e. the relative telomere length, calculated as the telomere to single copy gene ratio) at baseline with monochrome quantitative multiplex polymerase chain reaction (PCR). We used multivariable predictive linear regression to calculate mean differences and 95% confidence intervals (CIs) for the association between baseline telomere length and baseline characteristics. Results: The baseline characteristics of the 201 participants did not differ from those of the 805 participants in the parent trial population: 89% were male, the mean age was 39 years, 83.6% were Caucasian, 93% acquired HIV infection via sexual transmission, the mean estimated time since HIV diagnosis was 2.1 years, the mean HIV‐1 RNA load was 4.7 log10 HIV‐1 RNA copies/mL, the mean nadir and baseline CD4 counts were 301 and 324 cells/μL, respectively, and the mean CD4:CD8 ratio was 0.4. In the univariate analysis, shorter telomere length was associated with older age (per 10 years) ( P  <   0.001), HIV‐1 RNA ≥ 100 000 copies/mL ( P  =   0.001), CD4 count < 200 cells/μL ( P  =   0.037), lower CD4:CD8 ratio ( P  =   0.018), statin treatment ( P  =   0.004), and current alcohol consumption ( P  =   0.035). In the multivariable analysis, older age ( P  <   0.001) and HIV RNA ≥ 100 000 copies/mL ( P  =   0.054) were independently associated with shorter telomere length. Conclusions: Both age and HIV RNA viral load correlated with shorter blood telomere length in untreated persons living with HIV. These results suggest that HIV infection and age have synergistic and independent impacts upon immunosenescence.